The Dynamics of Intergenerational Family Abuse: A Focus on Child Maltreatment and Violence and Abuse in Intimate Relationships. (July 2015) - Abramovaite, Juste; Bandyopadhyay, Siddhartha; Dixon, Louise
The intergenerational cycle of violence hypothesis (often summarily described as 'violence begets violence') refers to assumptions or hypotheses about the consequences of child abuse and neglect in relation to a number of different outcomes, including its perpetuation across generations. This article reviews some of the channels by which this cycle of abuse can be perpetuated and suggests that this may occur without any genetic link. A mechanism for such transmission is suggested. It also critically analyzes the empirical literature and the implications of incorrectly identifying an intergenerational transmission mechanism. While the majority of the empirical papers find evidence of the intergenerational cycle, a large number of them do not control for endogeneity or have other methodological flaws. It discusses evidence on effectiveness of policies and concludes by pointing out the need for careful design to correctly capture the underlying relationship between experiencing childhood abuse and neglect and perpetrating child abuse in adulthood. JEL: Z13, I18